A Critique of Queer Phenomenology: Gender and the Sexual. Issue 3 (3rd July 2019) - Mulaj, Jeta
ABSTRACT: This article critiques Sara Ahmed's queer phenomenology in light of psychoanalytic theory of sexuality. I argue that there is a conspicuous absence of the unconscious, sexuality, and fantasy in Ahmed's Queer Phenomenology: Orientations, Objects, Others . I turn to the work of Jean Laplanche both to address this absence and to argue for a theory of the formation of sexuality and gender that is not exhausted by the phenomenal world.